Rangkaian Modalitas Kepedulian dari Struktur Generik Iklan Sirup ABC 2021 - Ignatia Evelyn Susanti Sitompul; Rustono Farady Marta; Cosmas Gatot Haryono (Universitas Negeri Medan, 2021)
The holy month of Ramadan is a month that is highly anticipated by the people of Indonesia. We can find various kinds of messages during the Holy Month of Ramadan. This certainly encourages many people to compete to present unique and creative messages, one of which is by using advertising media. One of the food categories that uses television as marketing media is syrup products. They are competing to make an advertisement that is interesting and of course unique so that it can attract the interest of the wider community. In 2017-2020, ABC became one of the syrups that Indonesians are interested in. The advertisement that is currently appearing, namely the ABC syrup ad ‘Berbagi Rasa Kebersamaan Dibulan Ramadhan’ will be examined using John Bateman's multimodal semiotics using interpretive qualitative methods. Through this research, the meaning contained in the advertisement namely concern for fellow family. Therefore, this research can be seen how the ABC syrup advertisement promotes its products as a brand that cares about the moment of Ramadan in the advertisement of Sharing the Feelings of Togetherness in the Month of Ramadan.